2018
DOI: 10.1051/matecconf/201824402006
|View full text |Cite
|
Sign up to set email alerts
|

Impact study of single stage and multi stage abrasive machining on static strength of lap adhesive joints of mild steel

Abstract: The article presents the results of research on the influence of one of the technological factors, which is preparation of C45 steel surface before bonding. Seven methods of surface preparation performed by mechanical abrasive grinding tools of different gradations: P40, P120, P320 and P500 in various combinations one-stage or multi stage and degreasing were analysed. The obtained results were subjected to a statistical one-way analysis of variance, which proved that the strength of the adhesive joints depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In the present work, increasing the ratio of valley depth to tip height as a result of changing the abrasive grain size, as evidenced by changes in the surface roughness parameters Ra, Rp, Rt and Rv, has a beneficial effect on the strength of adhesive joints. Rudawska et al [33] indicated that the properties of adhesive surfaces obtained after abrasive treatment with coated tools affect the strength of adhesive joints, and also indicated that the abrasive grain size significantly affects the strength of adhesive joints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, increasing the ratio of valley depth to tip height as a result of changing the abrasive grain size, as evidenced by changes in the surface roughness parameters Ra, Rp, Rt and Rv, has a beneficial effect on the strength of adhesive joints. Rudawska et al [33] indicated that the properties of adhesive surfaces obtained after abrasive treatment with coated tools affect the strength of adhesive joints, and also indicated that the abrasive grain size significantly affects the strength of adhesive joints.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of this type of defects could be due to the impact of large abrasive grains. However, it should be noted that the use of abrasive paper made it possible to obtain, in all cases, an undirected distribution of irregularities, which is advantageous when preparing the surface for the adhesive process [19].…”
Section: Surface Roughness and Topography Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step in the surface preparation process, after machining, was degreasing the surface. Degreasing is one of the most frequently used surface preparation operations performed just before the joining process, because it removes all kinds of dust and grease impurities, often remaining after previous processing [14,19]. Degreasing of steel sheet surfaces intended for bonding was carried out with technical acetone by spraying three times.…”
Section: Methods Of Steel Sheet Surface Preparationmentioning
confidence: 99%
“…Among the mechanical treatments, sandblasting is recommended and is the most favorable, while the coarse-grained abrasive cloth method is the least favorable. During sandblasting, it is to the use of an aluminium oxide, silicon carbide, and a quartz as the abrasives which is recommended due to their irregular shape and the sharp edges, making them effective in imparting a certain roughness to the treated surface [ 47 , 50 , 51 ]. Abrasives in the form of glass beads, porcelain beads, or metal shot should not be used on aluminium and its alloys, as they only cause surface crushing [ 52 ].…”
Section: Introductionmentioning
confidence: 99%